Thinkertoys : a handbook of creative-thinking techniques - Michalko, Michael, 1940- (Berkeley, Calif. : Ten Speed Press, 2006)
A guide designed to encourage creative thinking in business offers techniques, hints, and tricks for generating ideas and offers dozens of success stories.
Original spin -- Mind pumping -- Challenges -- Thinkertoys -- False faces (reversal) -- Slice and dice (attribute listing) -- Cherry split (fractionation) -- Think bubbles (mind mapping) -- Scamper (questions) -- Tug-of-war (force-field analysis) -- Idea box (morphological analysis) -- Idea grid (FCB grid) -- Lotus blossom (diagramming) -- Phoenix (questions) -- The Great Transpacific Airline and Storm Door Company (matrix) -- Future fruit (future scenarios) -- Brutethink (random stimulation) -- Hall of fame (forced connection) -- Circle of opportunity (forced connection) -- Ideatoons (pattern language) -- Clever Trevor (talk to a stranger) -- Chilling out (relaxation) -- Blue roses (intuition) -- The three B's (incubation) -- Rattlesnakes and roses (analogies) -- Stone soup (fantasy questions) -- True and false (Janusian thinking) -- Dreamscape (dreams) -- Da Vinci's technique (drawing) -- Dali's technique (hypnogogic imagery) -- Not Kansas (imagery) -- The shadow (psychosynthesis) -- The book of the dead (hieroglyphics) -- Warming up -- Brainstorming -- Orthodox brainstorming -- Raw brainstorming -- Murder board -- You are not a field of grass.
Includes index.
Original title: Thinkertoys : a handbook of business creativity for the '90s.
Keywords: Creative ability in business; Creative thinking